Risk Factors for Declines in Kidney Function in Sugarcane Workers in Guatemala. Issue 6 (June 2018) - Butler-Dawson, Jaime; Krisher, Lyndsay; Asensio, Claudia; Cruz, Alex; Tenney, Liliana; Weitzenkamp, David; Dally, Miranda; Asturias, Edwin J.; Newman, Lee S.
Abstract : Objectives: To characterize kidney function of sugarcane workers in Guatemala over the 6-month harvest and identify risk factors associated with changes in kidney function. Methods: Demographic and biological data were collected for 330 sugarcane cutters at the beginning and end of the harvest. Multivariable regression analyses were used to assess factors related to kidney function. Results: A decline in kidney function across the harvest was observed in 36% of the participants. Risk factors associated with this decline included working at a particular plantation mill, local area workers compared with highland workers, and current smokers. Conclusion: Results showed both occupational and behavioral factors play significant roles in declines in kidney function. These results underline the need for a comprehensive approach to the epidemic as well as further investigation of risk factors to guide research and interventions. Abstract : Supplemental Digital Content is available in the text